Multicultural Curriculum Development and Learning Model at the Ta'lim Sakinah Majelis (Universitas Negeri Semarang, 2022)
Majelis taklim is a non-formal educational institution whose followers are called non-student congregations. This is because the taklim assembly is a place for Islamic education that is not required as well as school students. The Ta'lim Council is recognized as one of the institutions that can encourage the realization of multiculturalism among Muslims. However, recently the Ta'lim Council has been accused of being one of the centers for the spread of religious radicalism. The multicultural, multiracial, and multireligious Indonesian society has a great potential for conflicts between groups, races, religions and ethnicities. On that basis, it is necessary to have a large role for educational institutions in developing learning models and developing the Multiculturalism Curriculum. The author conducted research on this matter at the Sakinah Ta'lim Council, Bandung City. This study uses a qualitative approach with analytical descriptive method. The results showed that the learning model applied in the Sakinah Ta'lim Council was a multicultural learning model that was not designed as a whole, but an insert model that was integrated into the learning material.